2013
DOI: 10.1209/0295-5075/102/57002
|View full text |Cite
|
Sign up to set email alerts
|

Majorana states in a p-wave superconducting ring

Abstract: The spectrum of excitations of the chiral superconducting ring with internal and external radii R i , R e (comparable with coherence length ξ) trapping a unit flux Φ 0 is calculated . We find within the Bogoliubov-deGennes approach that there exists a pair of precisely zero energy states when 2k ⊥ (R e − R i ) /π is integer (here k ⊥ is the momentum component in the disk plane while k ⊥ ξ > 1 ). They are not protected by topology, but are stable under certain deformations of the system. We discuss the ways to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It was shown that a magnetic field can be used to tune the Andreev state energy precisely to zero. The ZES are not topologically protected, but is "quenched" there [30]. They can be further manipulated by pinning of the skyrmions on columnar defects and nanoholes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was shown that a magnetic field can be used to tune the Andreev state energy precisely to zero. The ZES are not topologically protected, but is "quenched" there [30]. They can be further manipulated by pinning of the skyrmions on columnar defects and nanoholes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The Corbino geometry has been studied for small disk size, in which case the same zero energy criterion is found in the limit 2mv 2 F µ ∆ 2 0 by imposing Dirichlet boundary conditions on the wavefunctions directly. 63 direction ϕ. The resulting scattering rates display an average absolute deviation |ε| (averaged over the Fermi energy range in Fig.…”
Section: Majorana Bound States and Energy Splittingmentioning
confidence: 99%
“…The Corbino geometry has been studied for small disk size, in which case the same zero energy criterion is found in the limit 2mv 2 F µ ∆ 2 0 by imposing Dirichlet boundary conditions on the wavefunctions directly. 63 Appendix D: Surface-Bulk Scattering with Screened Disorder…”
Section: Majorana Bound States and Energy Splittingmentioning
confidence: 99%
“…Although the investigation of Majorana modes primarily focuses on single semiconducting wires, the path for Majorana detection and braiding often requires to employ more complex networks [16][17][18] or suggests alternative curved geometries, e.g. circular [19][20][21][22] and elliptical quantum rings [23].…”
mentioning
confidence: 99%